Optimal inventory replenishment and shipment policies in a four-echelon supply chain for growing items with imperfect quality. Issue 1 (1st January 2020) - Sebatjane, Makoena; Adetunji, Olufemi
ABSTRACT: Quality control is an important consideration in food production systems which often start with farming and processing operations and finish with consumption. This study develops an integrated inventory control model for a four-echelon supply chain (with farming, processing, screening and retail operations). The farmer grows newborn items and then delivers them to a processor once the items are mature enough. At the processing plant, the items are slaughtered, processed, packaged and screened for quality. The processor then delivers a certain number of equally sized batches of good quality processed inventory to the retailer who satisfies customer demand for good quality processed inventory. The processor sells the processed poorer quality inventory at a discounted price and as a single batch to secondary markets. The proposed supply chain inventory system is formulated as a profit maximisation problem with the number of batches of good quality processed inventory and the order quantity as the decision variables.